Learning form experts - Irene Valsecchi (Fondazione Eni Enrico Mattei (FEEM), 2008)
The survey is concerned with the issue of information transmission from experts to non-experts. Two main approaches to the use of experts can be traced. According to the game-theoretic approach expertise is a case of asymmetric information between the expert, who is the better informed agent, and the non-expert, who is either a decision-maker or an evaluator of the expert's performance. According to the Bayesian decision-theoretic approach the expert is the agent who announces his probabilistic opinion, and the non-expert has to incorporate that opinion into his beliefs in a consistent way, despite his poor understanding of the expert's substantive knowledge. The two approaches ground the relationships between experts and non-experts on such different premises that their results are very poorly connected.
Keywords: D81; L21; 330; Expert; Information Transmission; Learning; Entscheidung bei Unsicherheit; Sachverständige; Wissen; Asymmetrische Information; Entscheidungstheorie